Geronimo Stilton reporter. 12, Mouse house of the future - Stilton, Geronimo; Sicchio, Dario, 1990- (Stilton, Geronimo. Geronimo Stilton reporter, 2022)
When Professor Cheesewheel outfits busy editor-in-chief Geronimo Stilton's house with the latest technology to help keep it clean, the intrepid Geronimo is in for a future shock as his house goes haywire, leaving him with a mess bigger than before!